2016
DOI: 10.1186/s13007-016-0121-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reference genes for diurnal and developmental time-course real-time PCR expression analyses in lettuce

Abstract: BackgroundReal-time quantitative polymerase chain reaction (RT-qPCR) analysis is a low cost and sensitive technique that is widely used to measure levels of gene expression. Selecting and validating appropriate reference genes for normalising target gene expression should be the first step in any expression study to avoid inaccurate results.ResultsIn this study, ten candidate genes were tested for their suitability for use as reference genes in diurnal and developmental timecourse experiments in lettuce. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 44 publications
4
49
1
Order By: Relevance
“…4). Previous studies have suggested that unstable internal control genes will introduce significant errors in the qRT-PCR analysis, leading to misinterpretation of expression data [39][40][41][42]. Our results further confirm these views.…”
Section: Discussionsupporting
confidence: 89%
“…4). Previous studies have suggested that unstable internal control genes will introduce significant errors in the qRT-PCR analysis, leading to misinterpretation of expression data [39][40][41][42]. Our results further confirm these views.…”
Section: Discussionsupporting
confidence: 89%
“…As another suitable reference gene in the current paper, PP2A-4 was a good performer for different tissues and abiotic stress treatments in I. indigotica . Moreover, LsPP2A-1 was the most stable in diurnal and developmental timecourse experiments in Lactuca sativa (Sgamma et al, 2016). Similar results were observed in Malus domestica, PP2A-4 was recommended as the most suitable reference gene for all tissues and different biotic stresses (Kumar and Singh, 2015) and for abiotic stress and all sample sets in Sorghum bicolor (Reddy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative real-time (qRT)-PCR analysis was completed with the ABI QuantStudio 6 Flex system (USA), with each gene analysed in three biological replicates and three technical replicates. The LsPP2A-1 and ACTIN2 gene were used as an internal reference to normalize gene expression data for lettuce and Arabidopsis, respectively (Ding et al, 2015;Sgamma, Pape, Massiah, & Jackson, 2016). Fold change was calculated using the 2 −ΔΔCt method (Livak & Schmittgen, 2001).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%